Pendampingan dan Penguatan Masyarakat dalam Pencegahan Stunting Melalui Pembelajaran Lapangan Terpadu - Daru Purnomo; Sampoerno Sampoerno; Suryo Sakti Hadiwijoyo; Alvianto Wahyudi Utomo; Rendy H. Abraham; Rizki Amalia Yanuartha (Universitas Kristen Satya Wacana Salatiga, 2021)
The problem of stunting is a national issue that needs serious attention. In Salatiga City, stunting cases are still very ups and downs. This is because it is not only a matter of poverty, but also the low level of parenting and public understanding of stunting. The purpose of this community service is to aid and strengthen the community so that they have the ability to prevent stunting through Integrated Field Learning. So that it is expected to be able to raise public awareness of the causes of stunting problems that exist in each kelurahan, and to strengthen institutions at the base level which eventually becomes a synergistic movement. And aims to build an accurate database of the profile and potential of each kelurahan. The solution given is to aid and community strengthening through pentahelix collaboration with target communities in 7 Kelurahan namely Kauman Kidul Village, Pulutan Village, Kecandaran Village, Blotongan Village, Kotawinangun Lor Village, Tegalrejo Village and Randuacir Village where PLT has been carried out related to stunting cases found in Salatiga City, stunting prevention campaign. The method is carried out by making or looking for stunting prevention strategies, prevention action plans, socialization and workshops, making communication, information and education media in the context of stunting prevention campaigns, building data houses and reading gardens that can be accessed by the community as a source of family information, one of which is related to stunting prevention.